High serum IL-17A is associated with bone destruction in newly diagnosed multiple myeloma patients - Dong, Mengmeng; Zhang, Jinna; Chen, Qingxiao; He, Donghua; Yan, Haimeng; Zheng, Gaofeng; Han, Xiaoyan; He, Jingsong; Cai, Zhen (Frontiers in Oncology, 2022)
Background Multiple myeloma (MM) is a malignant proliferative disease of the blood system. The bone marrow microenvironment (BMM) is highly critical in the pathological process of MM. Many studies have shown that serum Interleukin-17A (IL-17A) plays a key role in various infectious diseases, autoimmune diseases, and cancers. However, few studies have focused on the influence of serum IL-17A level on multiple myeloma patients. Methods and Results A total of 175 MM patients were enrolled in this study. The multivariate linear regression analysis showed that serum IL-17A level in MM patients correlated with the degree of bone lesions and fracture incidence. Violin plot showed that MM patients with higher serum IL-17A level had more sever bone lesions and higher fracture incidence than that with lower serum IL-17A level. 171 patients were included in study of the relationship between serum IL-17A and best overall effect (BOE). We found that serum IL-17A level were independently related to the best inductive therapeutic efficacy, and the relationship was especially obvious in the light chain group. It could be deduced from the smooth curve that the higher the serum IL-17A level, the worse the BOE . The ROC prediction curve suggested that serum IL-17A could predict the BOE to a certain extent. A total of 148 MM patients were observed in the longitudinal study of relationship between serum IL-17A and PFS/OS. The Cox multivariate regression and K-M curve analysis with adjusted potential factors indicated that serum IL-17A levels in MM patients were not significantly correlated with PFS and OS. However, in the light chain group, the Cox multivariate regression and KM curve analysis indicated that MM patients with high serum IL-17A had worse PFS and OS compared to that with low serum IL-17A. Conclusion This observational study found that higher levels of serum IL-17A was independently correlated with higher severity of bone disease and fractures incidence in newly diagnosed MM patients. High erum IL-17A level was related with poor best therapeutic efficacy in light chain type. High serum IL-17A was also associated with poor PFS and OS in light chain type.